The Green Costs of Kelo: Economic Development Takings and Environmental Protection - Ilya Somin; Jonathan H. Adler (Washington University Law Review, 2006)
This Article provides the first detailed analysis of the environmental effects of Kelo and economic development takings generally. It contends that environmentalist support for economic development takings is misguided, and that the rule embodied by the Supreme Court’s Kelo decision is bad for property owners and environmental protection alike. There is a strong environmental rationale for strictly limiting or prohibiting the use of eminent domain for economic development. Part I of this Article briefly explains the rationales of the Kelo and Hathcock decisions and shows why a Hathcock-like ban on economic development takings is highly unlikely to impede environmental regulation or threaten the use of eminent domain for legitimate conservation purposes. The doctrinal rules advocated by the Hathcock Court and the Kelo dissenters, and adopted by courts in the eleven states that ban economic development takings, leave ample room for the use of eminent domain to advance environmental goals. This doctrinal point is buttressed by empirical evidence indicating that none of the eleven states with Hathcock-like bans on economic development takings have ever used this rule to block condemnation of property for environmental or conservation purposes. Part II shows that economic development takings may cause environmental harm. Allowing the use of eminent domain for economic development poses a particular danger to private conservation lands, agricultural lands, and open space. Because land owned by conservation nonprofits produces few economic benefits and does not contribute to tax revenue, it is likely to be targeted by developers and local governments that use eminent domain to advance their development interests. Economic development takings can also harm the environment by promoting environmentally harmful development, undermining property rights, and furthering dubious development plans that sap community wealth and reduce resources available for environmental protection. In many situations, economic development takings end up giving us the worst of both worlds: they cause environmental harm and reduce economic growth by transferring land to inefficient development projects.
Keywords: Economic development; Regulatory takings; Environmentalism; Eminent domain; Kelo v. City of New London 545 U.S. 469 (2005)